Population trends and distribution of the Lesser Snow Goose Anser caerulescens caerulescens in Japan, based on 50 years of monitoring - Sabano, Yutaka; Sawa, Yusuke; Uemura, Sachiko; Kurechi, Masayuki (Wildfowl, 2024)
Populations of the Lesser Snow Goose Anser caerulescens caerulescens, which historically bred and wintered in East Asia, declined from the 1800s and were almost extinct by the 1890s. In 1993, the “Restoration of Lesser Snow Goose to East Asia Project” was implemented, through cooperation by organisations from Japan, Russia and the United States of America. Since initiation of the project, Snow Geese have been regularly recorded in Japan, and numbers staging or wintering in Japan are still growing. Here, we study the population trends and distribution of Snow Geese wintering in Japan from 1971/72 (before the project commenced) to 2023/24. The mean (± s.d.) number of birds recorded in Japan over the last five winters (2019/20–2023/24) was 1,634 ± 196 geese, suggesting that a regular wintering population has become established in the country. We also collated information on colour-marked individuals. Geese marked in Anadyr (Russia) during the restoration project were found in Japan in subsequent years, suggesting that migratory traditions were also re-established. The extent to which the recent population increase recorded for Snow Geese in Japan was derived from the restoration project however remains unclear, because the exact location of the breeding grounds and migration routes of the Japanese-wintering birds are still unknown. Further studies (e.g. GPS tracking) therefore are required for a full evaluation of the success of this conservation initiative.